PEMERIKSAAN STATUS GIZI DAN PENGENALAN SARAPAN SEHAT PADA SISWA SDN No. 1 TIANYAR BARAT KUBU KARANGASEM - Indraguna P, G N.; Wirakusuma, IB; Dharmadi, M.; Sawitri, A.A. S; D.Y, P. Cintya (Buletin Udayana Mengabdi; Vol 12 No 2 (2013): Volume 12 No.2 – September 2013, 2013)
Efforts to improve the quality of human resources began with fulfilling their basic needs. Nutritional status is one indicator of the quality of human resources, especially in children of school age. Karangasem regency had the highest prevalence of underweight children in Bali. Based on the results of rapid survey of 10 children in the Elementary School no.1 of West Tianyar showed 2 (20%) students was underweight and only 1 of 10 children are said to usually take breakfast at home. Based on these, the initial thing that can be done is by detecting the nutrition status and socialization healthy breakfast at school. Socialization was conducted for 34 students in grade 4, 5 and 6 with teaching method. Nutritional status was examined from 31 students in grade 1,2 and 3. The measurement results were analyzed by the CDC Growth Charts for Children to assess the nutritional status of each student. The socialization went well and there was the improving knowledge about22.32%.The examination of nutritional status showed that the malnutrition status 14.3% in males and 17.6% in females. These activities were an initial way to improve the students’ knowledge whom are expected to continue their behavior of healthy nutrition at home. Ongoing activities are expected to monitor the nutritional status and children development, especially in Tianyar West village.